Desenvolvimento de biossensor enzimático baseado em lipases de fungo endofítico imobilizadas em Hidroxinitrato de zinco lamelar com nanopartículas de ouro para determinação de Carbendazim - Barboza, Adriene de Moura (2017)
In this work, was developed an enzymatic biosensor based on endophytic fungi lipases immobilized on lamellar zinc hydroxynitrate containing gold nanoparticles (HZnL/AuNPs). Initially, ninety fungi were pre-evaluated in terms of lipase production potential by fungal inoculation tests in a medium containing rhodamine-B dye and olive oil. After that, seven fungi were selected for the enzymatic activity determination, during eight days, using p-nitrophenyl palmitate (p-NPP) as substrate. Lipases hydrolytic activity was determined by spectrophotometry in the visible region (λ = 410 nm) monitoring the p-nitrophenol (p-NP) appearance as product of p-NPP hydrolysis catalyzed by lipase enzyme. The highest catalytic activity was obtained with Ceratobasidium sp.2 A1 fungus, resulting in 30.88 U (1.0 nmol of p-NP min-1 mL-1 μg -1 protein), on the eighth day of culture in liquid medium containing olive oil. The proposed biosensor was constructed with 0.5 U of lipase adsorbed in HZnL / AuNPs, graphite powder, multi-walled carbon nanotubes and mineral oil in the amounts of 20/90/10/50 mg, respectively. Square-wave voltammetry (SWV) was used for the biosensor optimization and application to the substrate p-nitrophenyl acetate (p-NPA), obtaining best electrochemical response with 80 Hz frequency, 2.0 mV scanning increment and 120 mV of pulse amplitude in 0.1 mol L-1 phosphate saline buffer solution (PBS) with 0.1 mol L-1 of NaCl, pH 7.0 and 50.0 mmol L-1 of the substrate. The lipase enzyme hydrolyzes the p-NPA substrate to p-NP, which is reduced electrochemically on the biosensor surface at -0.9 V vs Ag / AgCl, generating a peak proportional to the concentration of p-NPA. The biosensor was applied for pesticide carbendazim determination in water samples by the lipase inhibition method. The biosensor response for the carbendazim pesticide was linear in the range of 10 to 100 μg L-1 (r = 0.9981) with detection and quantification limits 3.13 μg L-1 and 9.50 μg L-1 respectively. The recovery study for carbendazim in fortified water samples ranged from 98.5 to 105.4%. The biosensor showed good repeatability (N = 15) and reproducibility (N = 5) with DPR of 4.4 and 3.6% respectively, remaining stable for 20 weeks. The results obtained by the biosensor application showed no significant differences when compared to the chromatographic reference method, with a confidence level of 99%, demonstrating the applicability of the biosensor for carbendazim pesticide determination.